2004
DOI: 10.1093/jhered/esi011
|View full text |Cite
|
Sign up to set email alerts
|

Evolution by Reticulation: European Dogroses Originated by Multiple Hybridization Across the Genus Rosa

Abstract: The European dogroses (Rosa sect. Caninae (DC.) Ser.) are characterized by a unique meiosis system ("canina-meiosis"), which controls the heterogamous development of tetraploid egg cells and haploid pollen grains resulting in a pentaploid somatic status. This permanent anorthoploidy is supposed to have originated by a hybridization event in the postglacial period. In this study we present molecular evidence by an analysis of nuclear ribosomal DNA data that dogroses are complex allopolyploids resulting from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 38 publications
7
105
0
Order By: Relevance
“…Silencing of rRNA genes in univalent, but not bivalent genomes Theoretical predictions based on secondary structure models have suggested that most ITS1 types are potentially functional in dogroses (Ritz et al, 2005). Although the GC content of the g-ITS clade is somewhat lower (55-56%) than that of the b (B59%)-clade, this difference is unlikely to mark the g-clade families as pseudogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of rRNA genes in univalent, but not bivalent genomes Theoretical predictions based on secondary structure models have suggested that most ITS1 types are potentially functional in dogroses (Ritz et al, 2005). Although the GC content of the g-ITS clade is somewhat lower (55-56%) than that of the b (B59%)-clade, this difference is unlikely to mark the g-clade families as pseudogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, unlike R. sects. Caninae and Rosa (Joly et al, 2006;Ritz et al, 2005), polyploidization does not seem to be an important factor in the evolution of R. sects. Chinenses and Synstylae.…”
Section: Introductionmentioning
confidence: 86%
“…Hybridization is easy for Rosa species because of overlapping distribution areas and flowering times, common generalist pollinators, and fertile crossbreeds (Jesse et al, 2006;Kevan et al, 1990;Matthews, 1920). Many studies have reported that hybridization has occurred in this genus not only between closely related species but also between species from different sections (Matthews, 1920;Mercure and Bruneau, 2008;Ritz et al, 2005;Schanzer and Kutlunina, 2010;Uggla and Carlson-Nilsson, 2005;Wissemann and Hellwig, 1997). Most species from sections Chinenses and Synstylae are diploid, but polyploidy is very common in other sections especially Caninae and Rosa.…”
Section: Low Resolution and Phylogenetic Incongruencementioning
confidence: 99%
See 1 more Smart Citation
“…Ser, Banksiae Lindl, Laevigatae Michx. and Bracteatae Thory., each of the four latter sections have only one to three species (RITZ et al 2005). Rehder's system was widely accepted and is still used as a basis for modern treatises (BAILEY 1963, WISSEMAN 2003, NYBOM 2009.…”
Section: Introductionmentioning
confidence: 99%